The examination of primary school students' attitudes toward science course and experiments in terms of some variables - Eren, C. Dilek; Bayrak, B. Karadeniz; Benzer, E. (ELSEVIER SCIENCE BV, 2015)
The purpose of this study was to determine the effects of gender, grade and type of school variables on the primary school students' attitudes toward science and technology course and science experiments. The study group is 247 students in 4th, 5th and 6th grades from three public schools and one private school in Istanbul in the semester of 2012-2013. Attitudes toward science and technology course and science experiments scale was used as a data collection instrument within the scope of this study. The scale was developed by Barmby et al (2005) and adapted to Turkish by Kaya and Boyu (2011). The data obtained were analyzed quantitatively using SPSS 16.00. T-test and One Way Anova test, and Kruskal -Wallis test for students' scores for attitudes toward science experiments were employed. In this study, it was found that students' attitudes toward science course didn't differ by gender and school type; however, there was a significant difference in terms of grade in favor of 6th grade. It was also found that students' attitudes toward science experiments didn't differ by gender and grade, however, there was a significant difference in terms of school type in favor of private school. As a result, the difference in favor of private school brings to mind the question how and how often is science taught using experiments in state schools? In this study, it is also recommended that pre-service science teachers should be taught the importance of making science experiments. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Attitude; science course; science experiments; primary school students; GRADE-LEVEL; CHILDRENS ATTITUDES; GENDER; INTERVENTION; TECHNOLOGY; Education & Educational Research; Social Sciences - Other Topics